CO2 sequestration and extreme Mg depletion in serpentinized peridotite clasts from the Devonian Solund basin, SW-Norway - Beinlich, Andreas; Austrheim, H.; Glodny, J.; Erambert, M.; Andersen, T. (2010)
The conglomerates of the Solund Devonian basin of SW-Norway contain numerous (locally up to 20vol.%) peridotitic clasts with concentric mm- to 10-cm thick zones of varying red to black color. The peridotite clasts show a clear, alteration-related textural evolution. The least-altered rocks are partly serpentinized peridotites, showing a typical mesh texture with veins of serpentine, magnesite and Ni-rich magnetite surrounding olivine (Fo91) relicts and its Mg-depleted, clay-like alteration product (deweylite assemblage). In the more advanced ophicarbonate stage, the mesh cells contain calcite, silica and are surrounded by talc. In the final stage, quartz, calcite, and hematite dominate the mineralogy and occur together with minor amounts of chromite, talc, Cr-chlorite, and Cr-hydroandradite. In tandem with this textural evolution is a decrease in MgO from 40 to 2.5wt% and a CaO increase from 1 to 35wt%. All peridotite clasts are characterized by high Cr and Ni concentrations. The chemistry and the textural evolution show that the clasts formed by an extreme Mg-mobilization from the peridotite, with development of secondary porosity and subsequent precipitation of calcite. MgO removed from the clasts after burial is in part consumed by replacement reactions in the sediment matrix around the clasts where Mg-free minerals (e.g., almandine) are replaced by Mg-bearing minerals (e.g., talc). Calculated apparent 87Sr/86Sr ratios of the clasts at 385Ma (0.7124-0.7139), corresponding to the inferred age of sediment deposition and incipient clast alteration, indicate interaction with diagenetic basinal fluids. We explain the reaction history as a three stage process involving (a) partial serpentinization of olivine in an oceanic environment (b) breakdown of olivine relicts to the deweylite assemblage resulting in mobilization of MgO under (near-) surface conditions in a tropical Devonian climate and (c) further Mg-mobilization and replacement of the deweylite assemblage by calcite and quartz after diagenesis. Sedimentary basins with abundant weathered peridotite represent potential sites for a permanent CO2 storage by formation of calcite in a low-temperature environment. © 2010 Elsevier Ltd.